2004
DOI: 10.1023/b:brea.0000025416.66632.84
|View full text |Cite
|
Sign up to set email alerts
|

The influence of clinical information on the accuracy of diagnostic mammography

Abstract: Our findings support the provision of clinical information relating to patients' presentation to radiologists reporting diagnostic mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…For instance, collateral clinical information may not be available for out-of-network patients whose medical data do not reside in the institutional electronic health record. Studies have demonstrated that insufficient clinical data available to the interpreting radiologist (ie, either cryptic or incorrect information) at the point of care increases the likelihood of a diagnostic miss [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, collateral clinical information may not be available for out-of-network patients whose medical data do not reside in the institutional electronic health record. Studies have demonstrated that insufficient clinical data available to the interpreting radiologist (ie, either cryptic or incorrect information) at the point of care increases the likelihood of a diagnostic miss [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Sites received institutional review board approval for study activities and for protection of the identities of women, to understanding variability in the interpretive performance of diagnostic mammography in community-based settings. Despite studies in which researchers considered characteristics at the level of the woman and mammogram ( 1,(3)(4)(5)(6)(7)(8), radiologist ( 9,10 ), and facility ( 11-13 ), broad unexplained variation remains in the performance of diagnostic mammography ( 1,9 ).…”
Section: Discussionmentioning
confidence: 99%
“…A false-negative (FN) diagnosis due to a perception or cognitive error is a recognised problem [1]. Evidence from earlier eye-tracking experiments using chest images reveals that most radiologists do not follow a systematic search strategy [2,3], and interpretation of these images can be influenced significantly by the clinical information provided by referrers [4][5][6][7]. Clinical information is provided as a guide for patient diagnosis and can be disease specific, symptom specific, location specific or a combination of these.…”
Section: Introductionmentioning
confidence: 99%